Russian Energy Strategies in the Natural Gas Market for Energy Security - Geng, Zhe (International Journal of Energy Economics and Policy, 2021)
The global natural gas market is one of the fastest growing energy markets. Russia is the second largest natural gas producerï¼Œand natural gas is its important strategic resource. As one of the main sectors of the Russian economy, natural gas plays a key role in the country's financial revenue and trade balance. In addition, it is also an important part of Russia's foreign policy. The structure and system of Russia's natural gas industry are inconsistent with its future development. We assess the natural gas security risks facing Russia by using HHI index, which takes into account the concentration of Russian natural gas exports. By calculating the HHI index, we found that Russia's natural gas export risk level differs considerably over different years. Russia is making efforts to promote the reform of the industry, and the government has constantly revised the draft energy strategy, to propose the latest derection for the long-term development of the natural gas industry. Russian gas strategy is to diversify the ways, directions and conditions of supplies to the world's major energy markets. Russia's layout of LNG export can helps boost trade growth, and promote the diversification of its natural gas exports. Keywords: Russia, Natural Gas, Energy Strategy, Energy Security JEL Classifications: Q4, Q40, Q48, C8 DOI: https://doi.org/10.32479/ijeep.10755